Role of preoperative versus post-operative HCG therapy in bilateral nonpalpable undescended testis - Gangopadhyay A; Sharma Shilpa; Bhushan V; Shukla R (Wolters Kluwer Medknow Publications, 2005)
To evaluate the role of human chronic gonadotropin (HCG) and compare the results when it is given preoperatively and postoperatively in bilateral nonpalpable undescended testes (BNUDT) to facilitate the surgical outcome. Sixty-six cases of BNUDT, from January 1997 to January 2004, were divided equally into two groups on a random basis: Group A - control group received HCG doses which were completed 7-10 days preoperatively and Group B - test group received postoperative HCG doses started 7-10 days after surgery. The HCG was given as per WHO recommendation. The results were assessed clinically, by color Doppler ultrasound and HCG stimulated testosterone assay. Standard orchidopexy was done in all cases. Both groups were comparable in terms of age, testicular size, and vascularity as assessed by the Doppler ultrasonographic study. The mean basal serum testosterone and the HCG stimulation were also comparable in both the groups. At the sixth week follow up, the difference in the serum testosterone level was statistically significant, Group A 60.50 + 7.19 ng/dl vs Group B 81.17 + 5.88 ng/dl. The testicular vascularity at the sixth week follow up was more in Group B (74% normal vs 55% normal). Sixteen (24%) testis were retracted in Group A, while none were in Group B. Postoperative HCG therapy has been proved to be more effective than conventional preoperative therapy for better surgical outcome in BNUDT.